(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The concept that guides "waiting for Godot" as a practical application of this philosophy also determines the work’s organisation. Therefore, Samuel Beckett, an absurdist playwright, abandoned the majority of conventional theatre’s logical structures. There isn’t much action that is considered dramatic. The aim of the characters is to emphasise that nothing occurs that would alter their lives. (Bigsby, 2004, page 24). This essay examines how our movement and the war relate to each other. More precisely, it discusses how the Second World War was the primary factor in the rise of absurdity as the largest movement throughout the stated time period. Our drama removes the plot and creates a timeless, circular quality as two lost creatures—typically portrayed as tramps—spend their days waiting, without knowing for sure who they are waiting for or if it will ever arrive. The absence principle underpins the play’s operation. The main character is never seen in it. One is largely silent out of the two that we do see. Movement is minimal or nonexistent. There isn’t much or no storyline. It appears that negativity is the guiding principle.